Assessment of Bone Metabolism in Male Patients With Benign Paroxysmal Positional Vertigo - Wu, Yunqin; Fan, Zhenyi; Jin, Hang; Guan, Qiongfeng; Zhou, Min; Lu, Xiaoxiong; Li, Li; Yan, Wang; Gu, Chengyao; Chen, Caijing; Han, Weiwei (Frontiers in Neurology, 2018)
Objective: Several studies have suggested a probable association between benign paroxysmal positional vertigo (BPPV) and both reduction of bone mineral density (BMD) and serum vitamin D levels, but none of these studies have explored their findings by examining bone turnover markers (BTM) in male idiopathic BPPV patients. This study aimed to evaluate the relationship between BMD and serum 25-hydroxyvitamin D (25(OH) D), with the occurrence of BPPV along with the characteristics of bone metabolism in male idiopathic BPPV patients. Methods: This retrospective study comprised 60 male idiopathic BPPV patients and 92 age-matched healthy controls referred to Ningbo No.2 Hospital during the period of February 2016 to February 2018. All subjects’ serum levels of 25(OH) D, bone formation marker amino-terminal propeptide of type I procollagen (PINP), and bone resorption marker β-isomerized carboxy-terminal telopeptide of type I collagen (β-CTX) were measured. BMD was determined by dual energy X-ray absorption at the lumbar spine and hip. Results: Among male patients with BPPV, the prevalence of BMD reduction was 35.0%, which was similar to that of 27.2% in healthy controls. There were significant differences in the mean serum 25(OH) D level and prevalence of vitamin D deficiency between the two groups, with p values of 0.049 and 0.009, respectively. The bone turnover markers of PINP and β-CTX in BPPV patients were lower than those in healthy controls. Logistic regression showed that vitamin D deficiency were associated with BPPV with an odds ratio of 3.8 (95% confidence interval=1.25–11.73) . Conclusion: Our study found that decreased serum vitamin D may be a risk factor for BPPV in male patients. The level of bone turnover among male patients with BPPV was lower than that among healthy controls.